Clinical and biological features of acute myeloid leukemia with MLL gene rearrangements in children and results of therapy according to protocols AML-MM-2000/2006 in the Republic of Belarus - Yu. A. Barovskaya; M. V. Stegantseva; O. V. Aleinikova (Онкогематология)
Objective of the study . Analysis of the treatment outcomes of patients with MLL rearrangements in the Republic of Belarus within protocols AML-MM-2000 and AML-MM-2006.Materials and methods . The study included 151 patients with newly diagnosed acute myeloid leukemia (AML) who were treated according to protocol AML-MM-2000 and AML-MM-2006. 11q23 abnormalities were detected in 40 (26.5 %) out of 151 patients.Results . The performed analysis of the survival outcomes of patients with 11q23 depending on the protocol showed that the probability of 5-year event-free survival (EFS) was significantly better (p = 0.0110) in children receiving treatment under protocol AML-MM-2006 (86 ± 13 %) compared with that of the patients included in protocol AML-MM-2000 (23 ± 12 %). Using protocol AML-MM-2006 allowed reducing the cumulative incidence of relapse (CIR) in this cohort from 46.2 ± 15.1 to 14.3 ± 14.3 % (p = 0.1609). EFS probability in recipients of allogeneic hematopoietic stem cell transplantation (alloHSCT) was 100 %, whereas in the group without alloHSCT – 31 ± 12 %, p = 0.0359. The treatment outcomes of patients with t(1;11) are comparable to those with CBF leukemia. The risk of relapse in patients with t(10;11) is higher than in the rest of the 11q23 cohort (62.5 ± 19.2 % versus 21.9 ± 7.5 %; p = 0.0136). CIR in patients with t(9;11) decreased from 42.8 % in protocol AML-MM-2000 to 15.4 % in protocol AML-MM-2006 (p = 0.1411).Conclusion . For the described cohort of patients alloHSCT is the best option for post-remission therapy. The worst prognosis is determined in patients with t(10;11), whereas the presence of t(1;11) is a favorable prognostic factor. Using the arm with cladribine showed to be effective in patients with t(9;11). To obtain reliable outcomes, we consider it reasonable to continue the study with the use of cladribine in patients with t(9;11).